2010 10th International Conference on Intelligent Systems Design and Applications 2010
DOI: 10.1109/isda.2010.5687185
|View full text |Cite
|
Sign up to set email alerts
|

An optoelectronic expert system for knowledge base systems

Abstract: In this paper a parallel optoelectronic computer architecture is proposed for expert systems in order to achieve high speed and high performance for parallel processing of rule-based systems. The proposed system is modeled and implemented using a two-dimensional space optics symbolic correlator to perform the comparison operations of the expert system. Also in this paper, an optoelectronic system for a parallel inference engine is presented. The proposed optical inference engine is able to perform 3D processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In this paper, the technique adopted is storing all the domain downloaded pages in a page oriented holographic memory (POHM) that can be efficiently realized and processed in parallel form. In the proposed system, both optical data and queries are encoded using optical symbolic substitution (coding rules) [20], [21] and Web page contents are encoded in binary matrices (patterns). The search algorithm is implemented using a set of logical operations in parallel.…”
Section: A Web Pages Encodingmentioning
confidence: 99%
“…In this paper, the technique adopted is storing all the domain downloaded pages in a page oriented holographic memory (POHM) that can be efficiently realized and processed in parallel form. In the proposed system, both optical data and queries are encoded using optical symbolic substitution (coding rules) [20], [21] and Web page contents are encoded in binary matrices (patterns). The search algorithm is implemented using a set of logical operations in parallel.…”
Section: A Web Pages Encodingmentioning
confidence: 99%
“…Decoding the output, transferring it to the memory, loading the inputs from the memory, and encoding them, in each cycle of the computation for large data planes is a nontrivial task, but is essential for an optical processor. Some authors suggested using external optical memories [24,30,68] (whose integration with the processor may be difficult), or transferring data via electronic buses [24,29,40,41]. In this paper we integrated the memory inside the processor (addressing Tucker's fifth issue about the unavailability of a satisfactory optical memory [69]).…”
Section: Comparisonmentioning
confidence: 99%
“…In fact, the studies for using optics for computing began more than five decades ago [1]. Especially in years 1980-1995, a large number of researchers invested in optical computing and presented several techniques to use optics in parallel processing, such as optical shadow casting [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], optical symbolic substitution [18][19][20][21][22][23][24], and optical vector-matrix multiplication [1,[25][26][27][28][29][30][31]. After this golden age of optical computing, it experienced a slowdown near the end of the last millennium.…”
Section: Introductionmentioning
confidence: 99%